Risk Aversion among Smallholder High-value Crop Farmers in the Southern Philippines - Sonny N. Domingo; Kevin A. Parton; John Mullen; Randall Jones (Philippine Institute for Development Studies (PIDS), 2015)
Several elicitation techniques were employed to gauge the attitudes to risk of smallholder high-value crop farmers in the southern Philippines. Results showed varying degrees of risk aversion, neutrality, and preference among smallholder farmers. Although some of the techniques classified distinct groups of local growers as either risk-averse or risk-preferring, the estimated risk aversion coefficients were relatively low signifying an inclination toward risk neutrality. These may partly explain the degree of openness or non-openness of smallholder farmers to cultural changes and development interventions. Variations in farmers' risk attitude classification among the different elicitation methods indicate the need for further validation studies and more definitive evaluation standards.
Keywords: 330; Philippines; risk attitude elicitation; farmers' risk aversion; smallholder high-value crop farming